(untitled) (Bangladesh Rice Journal, 2015)
Over the last two decades, Rice (Oryza sativa L.)-Maize (Zea mays L.) cropping systems have become one of the most dominant cropping systems in Bangladesh. This has coincided with the expansion in use of two-wheel tractors, which has facilitated options for minimum tillage. A three-year trial examined the prospects of conservation agriculture practices for Rice-Maize cropping in Bangladesh, with respect to minimum tillage and residue retention. Main plot tillage treatments of conventional full tillage, single pass wet tillage in rice (rotated with zero tillage in maize), bed planting and strip tillage were combined with residue retention treatments of 0, 50 and 100% in sub-plots. Compared to conventional tillage, minimum tillage saved 60-66% of fuel and 70-74% of labour required for land preparation. Although minimum tillage reduced the land preparation cost significantly through saving fuel and labour, weed infestation was higher compared to conventional tillage, which influenced the cost of production. Rice seedlings transplanted under unpuddled strip tillage required more time than in conventional or single pass wet tillage due to poor visibility of strips and the hard surface of untilled soil. Bed planting incurred the lowest production cost. Tillage methods and residue treatment produced no significant grain yield differences. Rice grown with single pass wet tillage and maize grown with strip tillage gave the highest gross margin over time. Despite lack of treatment effects on yields, the results suggest that profitability of Rice-Maize cropping could be increased with minimum tillage, provided there is adequate control of weeds by herbicides. Bangladesh Rice j. 2014, 18(1&2): 44-53